PERSEPSI MAHASISWA ATAS HASIL IMPLEMENTASI KEBIJAKAN UANG KULIAH TUNGGAL (UKT): STUDI PADA PTN DAN PTKIN BLU - Wardani, Amriza Nitra; Olfah, Sumadiyah T.; Santoso, Kurniawan; Wahyudi, Agus (JURNAL INFO ARTHA, 2025)
This study evaluates the implementation of the Single Tuition Fee (Uang Kuliah Tunggal/UKT) policy in ten state universities with Public Service Agency (BLU) status, emphasizing the role of UKT as a non-tax state revenue (PNBP) instrument within the framework of public financial management. The analysis was conducted based on students’ perceptions of UKT determination, service quality, and financing accessibility. The research employed a quantitative approach through the distribution of questionnaires, complemented by Importance-Performance Analysis (IPA) and the Customer Satisfaction Index (CSI). The findings show that more than 55% of students considered their UKT category misaligned with their family’s economic conditions. Although the overall student satisfaction index is relatively positive, the IPA indicates significant performance gaps, particularly in the provision of supporting facilities and campus infrastructure. In addition, UKT financing accessibility remains a challenge, with 28.65% of students reporting the need for additional financial support beyond parental contributions. Perceptual differences are also evident across university characteristics, particularly in Islamic state universities (PTKIN) and institutions located outside Java–Sumatra. These findings highlight the importance of improving transparency in UKT determination, enhancing BLU service quality, and strengthening student financing schemes to support a more equitable and sustainable public financial management system.